Os velhos Jogos Vorazes em um admirável mundo novo: paradigmas e rupturas na construção literária de personagens femininas em narrativas distópicas - Arboleya, Valdinei José (2023)
This research focused on an analysis of female characters in classic and contemporary dystopian novels. This theme was arrived at from reading other research on the subject and dystopian novels, which led to some questions that stood out as guiding the investigation, such as: Does the performance of female characters differ in these kinds of narratives regarding the ideological conceptions of patriarchal culture and the binary categorization that polarizes the sexes? Can this difference be linked to the performance and composition of the character the narrative focus and the authorship and creation process itself? Does this difference help contemporary dystopias to be classified as examples of narratives contrary to patriarchal hegemony? With the purpose of finding answers to this problematization, we defined as a general objective to analyze stereotypes and discourses about women, verifying how these cultural identity elements are symbolically recreated in classic and contemporary dystopian narratives and to compare the female characters performance in these narratives. To achieve these objectives, this research was based on the Comparative Literature assumptions, which works here as a theoretical and methodological research path. We also used literature sociocriticism, a theoretical approach used to analyze the texts and understand the creative processes of the social context. Thus, this is qualitative research, of bibliographic review in which we delimited as object of analysis the female characters of dystopian narratives, trying to analyze them from the ideological conceptions that led to maintenance of gender roles in dystopia. This also requires understanding the patriarchy concepts, such as identity, gender roles, female stereotypes, and social transformation. Therefore, this research proposed to analyze the classic dystopias Brave New World, by Aldous Huxley (1932), 1984, by Jorge Orwel (1949) and Farenheit 451, by Ray Bradbury (1953), comparing the female characters composition and performance to the characters from The Handmaid's Tale (1985) and The Testaments (2019), by Margareth Atwood, and The Hunger Games, by Suzanne Collins (2008). As a result of this investigation process, we note that contemporary dystopian narratives authored by women present a non-resigned response to the women condition in society and are deconstructionist productions in terms of gender roles ideological maintenance. These female-authored narratives introduce a new sense of being a woman about female submission, political action, and the capacity for social mobilization